New polymer electrolyte membrane for medium-temperature fuel cell applications based on cross-linked polyimide Matrimid and hydrophobic protic ionic liquid. (June 2021) - Rogalsky, S.; Bardeau, J.-F.; Makhno, S.; Tarasyuk, O.; Babkina, N.; Cherniavska, T.; Filonenko, M.; Fatyeyeva, K.
Abstract: New hydrophobic protic ionic liquid, 2-butylaminoimidazolinium bis(trifluoromethylsulfonyl)imide (BAIM-TFSI), has been synthesized. The ionic liquid showed good thermal stability to at least 350 °C. The conductivity of BAIM-TFSI determined by electrochemical impedance method was found to be 5.6 × 10 −2 S/cm at 140 °C. Homogeneous composite films based on commercial polyimide (PI) Matrimid and BAIM-TFSI containing 30–60 wt% of ionic liquid were prepared by casting from methylene chloride solutions. Thermogravimetric analysis data indicated an excellent thermal stability of PI/BAIM-TFSI composites and thermal degradation points in the temperature range 377 °C–397 °C. The addition of ionic liquid up to 50 wt% in PI films does not lead to any significant deterioration of the tensile strength of the polymer. The dynamic mechanical analysis results indicated both an increase of storage modulus E′ of PI/BAIM-TFSI composites at room temperature and a significant E′ decrease with temperature compared with the neat polymer. The cross-linking of the PI with polyetheramine Jeffamine D-400 allowed to prepare PI/Jeffamine/BAIM-TFSI (50%) membrane with E′ value of 300 MPa at 130 °C. The ionic conductivity of this cross-linked composite membrane reached the level of 10 −2 S/cm at 130 °C, suggesting, therefore, its potential use in medium-temperature fuel cells operating in water-free conditions. Highlights: New thermally stable hydrophobic protic ionic liquid BAIM-TFSI has been synthesized. The сomposite membrane based on polyimide Matrimid and BAIM-TFSI has been fabricated. The cross-linking of polyimide with polyetheramine Jeffamine improved its mechanical properties. The ionic conductivity of the composite membrane reached the level of 10 −2 S/cm at 130 °C.